Circulating Tumor Cells Were Associated with the Number of T Lymphocyte Subsets and NK Cells in Peripheral Blood in Advanced Non-Small-Cell Lung Cancer. (24th December 2017) - Ye, Liang; Zhang, Fang; Li, Huijuan; Yang, Linfei; Lv, Tangfeng; Gu, Wei; Song, Yong
Abstract : In this study, we aim to investigate the correlation between circulating tumor cells (CTCs) and the T lymphocyte subsets and NK cells in peripheral blood in non-small-cell lung cancer (NSCLC). The peripheral blood CTCs were determined by SET-iFISH. Flow cytometry was used to determine the distribution of T lymphocyte subsets and NK cells. Forty-one (49%) patients showed positivity for CTCs. Logistic regression analysis revealed CTC number was negatively correlated with the ratio of CD3+, CD4+, CD4+/CD8+, and NK % in patients at stage IV, while in a positive correlation was noticed between CTC number and regulatory T cell (Tregs) ratio in these patients. Multivariate analysis was performed in combination with the clinical-pathological materials to identify the risk factors for CTC positivity. Differentiation, NSCLC stage, percentages of CD3+CD4+ cells, Tregs, and NK cells were the independent risk factors for CTCs. CTCs were associated with the decrease of immune surveillance in the peripheral blood in NSCLC patients. The decrease of immune surveillance contributed to the escape of CTCs from the killing effects of the immunocytes, as well as the formation of metastasized lesions in the target organs.